The relationship between family planning methods, individual hygiene, and fertility with vaginal infections among the women referring to selected health centers in Isfahan city - Valiani, Mahboubeh (Medknow Publications Pvt Ltd, 2011)
BACKGROUND: With regard to the high commonality of vaginal infections among pregnancy-age women, especially gardnerella, candidiasis vaginitis, trichomonal vaginitis and chlamydia and by attending to this fact that these infections have a high cost, including the medical expenses and other services like missing working hours and bear a negative effect on the life quality of women as influential individuals in family and society, we decided to examine the commonality of some of these infections and their related factors among women referring to selected health centers in Isfahan City. METHODS: This research was of an analytical-descriptive type conducted on 266 samples referred to the midwifery unit of selected health centers in Isfahan City due to one of the common vaginal infections (gardnerella, candidiasis vaginitis, trichomonal vaginitis and chlamydia). The collection of data was carried out via conducting interview with women and filling out the researcher-made questionnaire with close-ended answers (38 questions) and open-ended answers (25 questions). Data analysis was done by descriptive and analytical statistics (variance analysis and chi-square test). RESULTS: The findings of the study showed a significant relationship (p = 0.04) between suffering from different kinds of vaginal infection and fertility factors (the treatment record of the spouse). But, there was no significant statistical relationship between suffering from these infections and delivery type, period regulation, seeing stains and the pregnancy prevention type. Meanwhile, a significant relationship was found between suffering from vaginitis and demographic and individual factors like women's job (p=0.001), their educational level (p = 0.006), body mass index (p = 0.01) and their weight (p = 0.02). However, no significant relationship was found between suffering from common vaginal infections and individual health factors. CONCLUSIONS: With regard to the research findings, knowledge of the factors related to vaginal infection, including the fertility factors, can be instrumental in preventing and reducing the suffering from these infections. Therefore, training related to mothers’ educational level and consulting with women for knowing the susceptibility factors like the effect of weight, attending to mothers’ professional issues and prevention methods by following individual and sexual health-related issues by men and women can reduce the rate of suffering from these infections and promote the health level of mothers and hence, the society's health status.